2016
DOI: 10.1620/tjem.240.39
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Levels of Pentraxin 3 Are Associated with Poor Prognosis of Colorectal Carcinoma Patients

Abstract: Colorectal carcinoma (CRC) is one of the most common cancers globally. It is essential to identify a prognostic predictor for CRC. Pentraxin 3 (PTX3) is a glycoprotein that is secreted by a variety of human cells. It plays an important role in inflammation and immune regulation. Increasing evidence reveals that elevated PTX3 expression is related to poor prognosis in various cancers. The aim of the study was to determine the usefulness of plasma PTX3 level as a prognostic predictor in CRC. Total 184 CRC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Thus, although PTX3 serves as a useful prognostic biomarker for CRC, the optimum cut-off value for the PTX3 may differ in various studies enrolled patients with different stage, or different endpoint and statistics mothed. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although PTX3 serves as a useful prognostic biomarker for CRC, the optimum cut-off value for the PTX3 may differ in various studies enrolled patients with different stage, or different endpoint and statistics mothed. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer patients, circulating levels of PTX3 were higher compared to patients with prostatic inflammation, while serum levels of prostate-specific antigen (PSA) and CRP were not different between the two groups (134). In CRC, PTX3 circulating levels were significantly increased compared to healthy individuals or to patients with colorectal polyps, representing an independent prognostic factor for CRC patients (135). PTX3 levels were reduced at discharge after surgery, and a subsequent increase during the follow-up was associated to recurrence.…”
Section: Ptx3 As Marker Of Cancer Progressionmentioning
confidence: 99%
“…69 In addition, Zhang et al found that increased PTX3 was related to the poor prognosis of patients with CRC, and confirmed that PTX3 was an independent prognostic factor for CRC. 70 Carmo et al found that PTX3 polymorphism was associated with the incidence of hepatitis C. The polymorphism of PTX3 rs2305619 and plasma level were associated with liver cancer patients with Child grade B and C, while PTX3 seemed to be a risk factor for patients with liver cancer and chronic hepatitis C. 71 In summary, TNFAIP5 or PTX3 overexpression in tumors might indicate the risk of disease recurrence and metastasis, and it could be a prediction and prognostic factor for patients with malignant tumors.…”
Section: Tnfaip5 and Malignant Tumorsmentioning
confidence: 99%